The Effectiveness of Link Village Financial System (Siskeudes) and Cash Management System (CMS) - Calvina Berlianti Rahmah; Mirna Amirya (ARBITRASE: Journal of Economics and Accounting, 2025)
This qualitative case study research aims to analyze the effectiveness of using the Village Financial System (Siskeudes) application, namely Siskeudes Link, and Cash Management System (CMS), identify the constraints, and find solutions to these constraints using the DeLone and McLean Information System Success Model. The research data were collected through direct interviews with seven informants from five villages in Malang Regency who had provided system assistance, direct observation of system usage, and implementation documentation. This study finds that Siskeudes Link and CMS had been running quite effectively both in terms of system quality and information quality, although constraints remained. In addition, the quality of service was also adequate even though users felt that additional features were needed. The use of the system had also been maximized according to the needs of the village apparatus, while the net benefits had been felt by users, although the system did not affect village expenditures and decision-making. Of the 21 indicators analyzed, 19 were found to be effective. However, 10 indicators still encountered challenges, including double transactions and input process issues, which have been addressed with data import and feature enhancements.